Perencanaan dan Perancangan Rekreasi Agrowisata di Desa Petang, Badung Utara - I Putu Andre Yogi Prasetya; I Nyoman Gede Mahaputra; Made Anggita Wahyudi Linggasani (Program Studi Arsitektur, Fakultas Teknik Universitas Warmadewa, 2022)
Badung Regency has a diversity of tourism, for example art-cultural tourism, commercial, food, and spiritual tourism, nature, agrarian and spiritual tourism. However, tourism in North Badung is still quite small, therefore there is a need for an alternative form of tourism that can support the potential in North Badung which is famous for its uniqueness, namely Agrarian Tourism. Petang Village which has an area of about 115.00 kmÂ² and is located in the highlands so that the air there feels cool which makes Petang Village famous for its agricultural and plantation sectors. There is still very little agriculture-based tourism in Petang Village, there is no room for education about agriculture and there is no room for managing and utilizing plantation crops in Petang Village. The purpose of Agro-tourism Recreation Planning and Design in North Badung, Bali is to design and plan agro-tourism facilities that are useful for the general public to promote tourism in the North Badung area, make Petang Village an agricultural tourism destination and a place to educate about agricultural crops. This report uses the method of literature study, field observation, documentation and interviews. This report produces a schematic design which is then realized in the design development in the form of a building form.